When my bike flies and other stories level 4 - Horsburgh, Nicholas (Karachi : Oxford university press, 2023)
"When My Bike Flies and Other Stories" (Level 4, Oxford) is a collection of engaging stories for young readers. The title story, "When My Bike Flies," is about a boy who dreams of making his bike fly, showcasing imagination and adventure. The other stories explore themes of creativity, friendship, and overcoming challenges. Written in accessible language for level 4 readers, the book encourages curiosity and highlights the importance of dreaming big and problem-solving.
Keywords: English : Short stories; Oxford : level 4